Changes in Bargaining Status and Intra-Plant Wage Dispersion in Germany. Much Ado about Nothing? - John T. Addison; Paulino Teixeira; Katalin Evers; Arnd Kölling (Global Labor Organization (GLO), 2017)
A number of studies have reported that union decline is associated with rising overall wage inequality, not least in Germany where the phenomenon has been linked to economic resurgence. The present paper takes an unconventional approach to this potential source of rising inequality by examining intra-plant wage dispersion in the wake of establishments exiting from or entering into collective bargaining. Our estimation strategy hinges upon the identification of comparable groups of establishments and on both short-run and medium- to long-term changes in the wage structure. Using two main empirical strategies, we report at most a modest widening effect on dispersion for plants abandoning collective agreements. The converse does not apply for those establishments joining collective agreements. These two effects cast doubt on some of the more exaggerated claims as to the importance of deunionization to wage inequality.
Keywords: J31; J51; J53; 330; Germany; sectoral collective bargaining; deunionization; intra-plant wage inequality; changes in bargaining status